(untitled) (Journal of Current and Advance Medical Research, 2018)
Background: The clinical and demographic profiles of pregnant women with diabetes mellitus are very important consideration during management. Objectives: The purpose of the present study was to see the clinico-demographic characteristics of pregnant women with diabetes mellitus attended at a referral diabetic care hospital in Bangladesh. Methodology: This cross sectional study was carried out in inpatient Department of Obstetrics and Gynecology and in outpatients Department of Radiology and Imaging of Bangladesh Institute of Research and Rehabilitation for Diabetes, Endocrine and Metabolic Disorders (BIRDEM) at Dhaka, Bangladesh during the period of April 2005 to March 2007 for a period of two (02) years. Pregnant women diagnosed as diabetes mellitus or gestational diabetes mellitus (GDM) selected for caesarean section or induction of labour, gestational age 236 weeks having 23700 gm by clinical method were included in this study. All the clinical relevant data and demographic characteristics were recorded. Result: A total number of 69 pregnant women with diagnosed DM or GDM were recruited for this study. The mean (+SD) age of the patients was 30.8±5.1 years ranged from 20 to 40 years. 60.9% patients were from middle socioeconomic class, 30.4% from low and 8.7% from high class. 58.0% had DM and 42.0% had GDM. The mean (1SD) gestational age of the patients was 37.511.5 weeks range from 36 to 41 weeks. Conclusion: In conclusion majority of the pregnant women are in the middle age group with the middle income group. Journal of Current and Advance Medical Research 2017;4(2):36-39